Man Power Productivity Hcd dengan Wosa (Works Sampling Analysis) - Danang Cahyanugroho (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
PT.PN focused on the mining and energy sector contractors. Then it is trusted to work on quary, limestone, clinker, dam construction and road construction. PT PN has human capital development department that is tasked with managing the systems an processes of human resource development through the formulation of development strategies in line with rodmap people of Astra an PT PN. Increase organization effectiveness either by increasing manpower productivity. The research aims to improve the performance of human resources is closely related to man power productivity. One way to increase the contribution and value of human resources by using work sampling analysis method. This study involved five employees in the human caiptal development departement. Consisting of three people as the human caiptal learning an leadership development officer, one person inthe data management officer, and one person as the human capital development admin. Based on the measurement resuts of work sampling analysis, employeesin the HCD department have performed their duties effectively. This can be seen from the total employees man activity of 67,87%, support activity of 24,3% and allowance of 7,8%. The increase in the contribution and value of human ressources will directly affect the increase in man power productivity.